4(2x-8)-(3x+7)=5(2x+1)-14

Simple and best practice solution for 4(2x-8)-(3x+7)=5(2x+1)-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-8)-(3x+7)=5(2x+1)-14 equation:



4(2x-8)-(3x+7)=5(2x+1)-14
We move all terms to the left:
4(2x-8)-(3x+7)-(5(2x+1)-14)=0
We multiply parentheses
8x-(3x+7)-(5(2x+1)-14)-32=0
We get rid of parentheses
8x-3x-(5(2x+1)-14)-7-32=0
We calculate terms in parentheses: -(5(2x+1)-14), so:
5(2x+1)-14
We multiply parentheses
10x+5-14
We add all the numbers together, and all the variables
10x-9
Back to the equation:
-(10x-9)
We add all the numbers together, and all the variables
5x-(10x-9)-39=0
We get rid of parentheses
5x-10x+9-39=0
We add all the numbers together, and all the variables
-5x-30=0
We move all terms containing x to the left, all other terms to the right
-5x=30
x=30/-5
x=-6

See similar equations:

| 3x−1=2x+39 | | 70=5x+8+7x+2 | | c+5/8=-9/16 | | -4x+11=5=6(-x+3) | | 7(−4x−5)=6x+2 | | -9-6c=5c+11-c | | 0.60x-6=14 | | Z2+12z+36=0 | | 67-25x=350 | | 9x^2-61x+26=0 | | 15-k=-19+k | | -6+8k=-46 | | -24=8x+16 | | x=140-60 | | 2(-2x-6)=-60 | | 2x²/5+5x/4=0 | | 2x-3(x+4)=8-5x | | (20x+4)+(90)=180 | | 25x-350=67 | | 2(5x-8=104 | | -4y=7.4-3.6y | | 6m-2=m=3 | | Y=(4x-5)⁶ | | 5x+8=-10-x | | 16=-2(-7+a) | | 6(10-2x)=-72 | | 5(x-5)+11=2(x+4) | | -7(4+2x)=-182 | | 1.5=d/3 | | 2​p​-12=12-2​p | | 7-6x-3=-20+3x-12 | | 10(x+6)=120 |

Equations solver categories